The Mechanism of Political Investment or How and Why Business Participates in Elections and Pays Parties? - БарсуковаСветлана Юрьевна; ЗвягинцевВасилий Иванович (Journal of Economic Sociology, 2010)
The key task for the authors of the paper is to show that besides standard procedure of purchasing administrative services there is a formatted process of “political investment” when business buys not services or a bureaucrat but a place in the authority and puts his own representative and pays for that by shadow recourses. The basis for the research is the interviews with those who is involved in the process of political interest formation and acquainted with shadow economy and shadow political issues. The interviews were taken within the project “Jointing shadow economy and shadow policy” funded by HSE. The authors analyze how, in what forms and why are the shadow economic recourses invested into the political sphere.